2016
DOI: 10.1093/jme/tjw150
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Sand Fly,Psathyromyia elizabethdorvalaesp. n. (Diptera: Psychodidae: Phlebotominae), From Brazil

Abstract: A new species of phlebotomine sand fly, Psathyromyia elizabethdorvalae sp. n. Brilhante, Sábio & Galati from Xapuri, Acre state, Brazil, is described, with illustrations of male and female adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Psathyromyia elizabethdorvalae Brilhante, Sábio & Galati, 2017 (1 ♂, Figure 2C) was found in a small ombrophylous forest fragment (63°19'52.5"W, 10°15'37.8"S) in Monte Negro municipality. Records of this species have been made in other regions of the Amazon basin, primarily in forest and peridomicile environments in Xapuri municipality, Acre State (Brilhante et al, 2017).…”
Section: (With 2 Figures)mentioning
confidence: 99%
“…Psathyromyia elizabethdorvalae Brilhante, Sábio & Galati, 2017 (1 ♂, Figure 2C) was found in a small ombrophylous forest fragment (63°19'52.5"W, 10°15'37.8"S) in Monte Negro municipality. Records of this species have been made in other regions of the Amazon basin, primarily in forest and peridomicile environments in Xapuri municipality, Acre State (Brilhante et al, 2017).…”
Section: (With 2 Figures)mentioning
confidence: 99%
“…Such epidemiological scenario has motivated several researchers to undertake projects to investigate the phlebotomine fauna with a view to identifying possible vectors. Data from the literature indicate that Acre presents a great diversity of species, by the end of 2008, 52 species had been reported (Azevedo et al 2008); later 16 new records (Teles et al 2013a(Teles et al , 2016 and three new species (Teles et al 2013a, De Oliveira et al 2015, Brilhante et al 2017 were reported, with a total of 71 species of sand fly. However, Lu.…”
Section: Short Communicationmentioning
confidence: 99%
“…The Amazon region is considered endemic for American Cutaneous Leishmaniasis (ACL), and studies have been concentrated on the vectorial role of phlebotomine sand flies. However, there are still incipient studies on the ecological and biological aspects of the phlebotomine fauna in the state of Acre, which is rich and diverse with recent descriptions and new records of species (Tojal et al 2006, Teles et al 2013, 2016, Araújo-Pereira et al 2014, Brilhante et al 2017). The present study had, as its objective, to report the first record of Sciopemyia vattierae (Le Pont & Desjeux, 1992) in Acre and Brazil, which increases the number of species for this state and for Brazil.…”
Section: Introductionmentioning
confidence: 99%